Ta’ṯīr Istirātijiyyah al-‘Asf aḏ-ḏihny (Brainstorming) ‘ala Ta’līm Mahārah al-Qirāah Laday Thalabah aṣ-Ṣaffi al-‘Āsyir fi al-madrasah al-Āliyyah al-Hukūmiyyah al-Wāhidah Padang - Marlina Batubara; Asrina; Rahmawati (Taqdir, 2026)
This study aims to determine the effectiveness of the brainstorming learning strategy and its impact on students’ reading skills. The research employed a quantitative experimental method with a pre-test and post-test design involving 30 tenth-grade students. Data were collected through tests, observations, interviews, and documentation. The data were analyzed using a t-test with the assistance of SPSS version 25 after passing the normality and homogeneity tests. The results showed that students’ initial maharah qira’ah abilities in both groups were categorized as low, with the average pre-test scores of 57 for the control group and 46.33 for the experimental group. After the implementation of the strategy, the average score of the experimental group increased to 85.33, while the control group only reached 72.66. These findings indicate that the brainstorming strategy is effective and has a significant positive effect on improving students’ reading skills.